Impact of the Helicoidal Geometry on the Magnetic Properties of Permalloy Nanowires for Spintronic Applications - Escrig-Murua, J; Saavedra-Díaz, E (Elsevier B.V., 2025)
This study investigates the static and dynamic magnetic properties of helically shaped permalloy nanowires through micromagnetic simulations. We performed comprehensive numerical analyses to simulate hysteresis curves under an externally applied magnetic field aligned along the z-axis, focusing on the impact of the helicoidal geometry on the magnetic reversal mechanism. Our results reveal that, under specific geometric conditions, magnetization reverses through three distinct mechanisms. In Region I, vortex-type domain walls with varying chirality propagate at the top and bottom of the nanowire. In Region II, these walls exhibit uniform chirality at both ends, while in Region III, vertical vortices dominate. Additionally, we examined the dynamic susceptibility of the nanowires in the frequency range of 0–20 GHz. We found that varying the degree of helicoidal geometry influences both the position and the number of resonance peaks. Beyond these fundamental insights, our study highlights the potential applications of helically shaped nanowires in advanced magnetic sensing, data storage, and nanoscale spintronic devices. © 2024 Elsevier B.V.